2015
DOI: 10.1088/0256-307x/32/10/106801
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of InAs 1– x Sb x with Different Sb Compositions on GaAs Substrates

Abstract: InAs1−𝑥Sb𝑥 with different compositions is grown by molecular beam epitaxy on (100)-oriented semi-insulating GaAs substrates. The increase of Sb content in the epilayer results in the deterioration of crystal quality and surface morphology. Hall measurements show that the carrier concentration increases with the composition of Sb. The electron mobility decreases initially, when Sb composition exceeds a certain value, and the mobility increases slightly. In this work, we emphasize the comparison of crystal qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…As can be seen in the figure, the fraction of Sb into the layer is linearly dependent on the Sb/In flux ratio, provided that the As flux is constant (1.06 × 10 −6 Torr). The same dependence was reported by Yen et al [9] and Marcadet et al [20] . Essentially, the composition x could be readily controlled over the range 0 ≤ x ≤ 0.71.…”
Section: Resultssupporting
confidence: 87%
“…As can be seen in the figure, the fraction of Sb into the layer is linearly dependent on the Sb/In flux ratio, provided that the As flux is constant (1.06 × 10 −6 Torr). The same dependence was reported by Yen et al [9] and Marcadet et al [20] . Essentially, the composition x could be readily controlled over the range 0 ≤ x ≤ 0.71.…”
Section: Resultssupporting
confidence: 87%
“…Indeed, when the external field was applied to the cell containing the mixture of PCb and SiO 2 particles dried at 90°C or the mixture of PCb and ethanol (20:1), we found depositions on the ITO cathode, which could be the polyalkenes produced by the electrochemical reduction of ethanol. [ 21 ] The above experiments suggested that “high voltage” and “reducible substance” were the essential conditions for an electrochemical reduction on ITO cathode, and its occurrence severely affects the reversibility. The weak‐polar ERPC worked at low voltages, which avoided the electrochemical reduction and thereby gained good reversibility.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the high incorporation of Sb in the InAs 0.45 Sb 0.55 epitaxial layer introduces a lattice mismatch of about 3.2% with respect to the GaSb substrate, which will degrade the material quality and the performance of the photodetector. [26] Thus, only by increasing the incorporation of Sb in the InAs 1−x Sb x quantum is unable to extend the wavelength from the eSWIR to the MWIR region.…”
Section: Resultsmentioning
confidence: 99%